IMPLEMENTASI PROGRAM KAMPUS MENGAJAR DI SEKOLAH DASAR SWASTA NURANI JAKARTA - Khusnul Fatonah; Alfian Alfian; Sri Lestari (Universitas Negeri Medan, 2021)
Abstract: Implementation Of The Kampus Mengajar Program At The Nurani Private Elementary School Jakarta. Kampus Mengajar is part of the program Merdeka Belajar Kampus Merdeka (MBKM) aims to help elementary schools affected by the COVID-19 pandemic. One of the schools targeted by this program is the Nurani Private Elementary School Jakarta.The purpose of this research is to find out and analyze how the implementation of the Kampus Mengajar Program is in the target schools by referring to the theory of implementation of David C. Korten and its relation to literacy, numeracy, technology adaptation, and administration activities in the target schools. The method used in this research is descriptive qualitative with data collection in the form of interviews, observations, and documentation. The results of the study explained that the implementation of the Kampus Mengajar Program at SDS Nurani went well. This is reviewed based on the aspects of the suitability of the program with the target, the program with the implementer, and the implementer with the right target. Literacy activities carried out by students are helping students in reading and writing. In the field of numeracy, students teach students various forms of mathematical calculations and their solutions. The technological adaptations carried out by students at SDS Nurani are to help teachers create interesting learning media and help use various online applications for learning. In terms of administration, students assist teachers in correcting student assignments and exams, supervising exams for grade 6 students, and helping fill out e-reports.Keywords: Implementation, Kampus Mengajar Program, SDS NuraniAbstrak: Implementasi Program Kampus Mengajar di Sekolah Dasar Swasta Nurani Jakarta. Kampus Mengajar merupakan bagian dari program Merdeka Belajar Kampus Merdeka (MBKM) yang bertujuan untuk membantu sekolah- sekolah dasar yang terdampak pandemi COVID-19. Salah satu sekolah yang menjadi sasaran program ini adalah Sekolah Dasar Swasta Nurani Jakarta. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana implementasi Program Kampus Mengajar di sekolah sasaran dengan mengacu pada teori implementasi David C. Korten dan keterkaitannya dengan kegiatan literasi, numerasi, adaptasi teknologi, dan administrasi di sekolah sasaran. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menjelaskan bahwa implementasi Program Kampus Mengajar di SDS Nurani berjalan dengan baik. Hal ini ditinjau berdasarkan aspek kesesuaian program dengan sasaran, program dengan pelaksana, dan pelaksana dengan sasaran yang sudah tepat. Kegiatan literasi yang dilakukan mahasiswa adalah membantu siswa dalam membaca dan menulis. Dalam bidang numerasi, mahasiswa mengajari siswa beragam bentuk perhitungan matematika beserta penyelesainnya. Adaptasi teknologi yang dilakukan mahasiswa di SDS Nurani adalah membantu guru membuat media pembelajaran yang menarik dan membantu penggunaan berbagai aplikasi daring untuk pembelajaran. Dalam hal administrasi, mahasiswa membantu guru-guru untuk mengoreksi tugas dan ujian siswa, mengawasi ujian siswa kelas 6, serta membantu mengisi e-raport.Kata kunci: Implementasi, Program Kampus Mengajar, SDS Nurani